Hyperglycemia Induces a Dynamic Cooperativity of Histone Methylase and Demethylase Enzymes Associated With Gene-Activating Epigenetic Marks That Coexist on the Lysine Tail - Brasacchio, Daniella; Okabe, Jun; Tikellis, Christos; Balcerczyk, Aneta; George, Prince; Baker, Emma K.; Calkin, Anna C.; Brownlee, Michael; Cooper, Mark E.; El-Osta, Assam (Diabetes (New York, N.Y.), 2009)
Hyperglycemia Induces a Dynamic Cooperativity of Histone Methylase and Demethylase Enzymes Associated With Gene-Activating Epigenetic Marks That Coexist on the Lysine Tail Daniella Brasacchio 1 , Jun Okabe 1 , Christos Tikellis 2 , Aneta Balcerczyk 1 , Prince George 1 , Emma K. Baker 1 , Anna C. Calkin 2 , Michael Brownlee 3 , Mark E. Cooper 2 , 3 and Assam El-Osta 1 1 Epigenetics in Human Health and Disease Laboratory, The Alfred Medical Research and Education Precinct, Baker IDI Heart and Diabetes Institute, Victoria, Australia; 2 Junvenile Diabetes Research Foundation (JDRF) Danielle Alberti Centre for Diabetic Complications, Diabetes Division, Baker IDI Heart and Diabetes Institute, The Alfred Medical Research and Education Precinct (AMREP), Melbourne, Victoria, Australia; and 3 JDRF International Center for Diabetic Complications Research, Albert Einstein College of Medicine, Bronx, New York. Corresponding author: Assam El-Osta, assam.el-ostaatbakeridi.edu.au . Abstract OBJECTIVE Results from the Diabetes Control Complications Trial (DCCT) and the subsequent Epidemiology of Diabetes Interventions and Complications (EDIC) Study and more recently from the U.K. Prospective Diabetes Study (UKPDS) have revealed that the deleterious end-organ effects that occurred in both conventional and more aggressively treated subjects continued to operate >5 years after the patients had returned to usual glycemic control and is interpreted as a legacy of past glycemia known as “hyperglycemic memory.” We have hypothesized that transient hyperglycemia mediates persistent gene-activating events attributed to changes in epigenetic information. RESEARCH DESIGN AND METHODS Models of transient hyperglycemia were used to link NFκB-p65 gene expression with H3K4 and H3K9 modifications mediated by the histone methyltransferases (Set7 and SuV39h1) and the lysine-specific demethylase (LSD1) by the immunopurification of soluble NFκB-p65 chromatin. RESULTS The sustained upregulation of the NFκB-p65 gene as a result of ambient or prior hyperglycemia was associated with increased H3K4m1 but not H3K4m2 or H3K4m3. Furthermore, glucose was shown to have other epigenetic effects, including the suppression of H3K9m2 and H3K9m3 methylation on the p65 promoter. Finally, there was increased recruitment of the recently identified histone demethylase LSD1 to the p65 promoter as a result of prior hyperglycemia. CONCLUSIONS These studies indicate that the active transcriptional state of the NFκB-p65 gene is linked with persisting epigenetic marks such as enhanced H3K4 and reduced H3K9 methylation, which appear to occur as a result of effects of the methyl-writing and methyl-erasing histone enzymes. Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Received December 2, 2008. Accepted February 3, 2009. Readers may use this article as long as the work is properly cited, the use is educational and not for profit, and the work is not altered. See http://creativecommons.org/licenses/by-nc-nd/3.0/ for details. © 2009 by the American Diabetes Association.